Sida vid sida - Birgitta Meurling; Ann-Christine Norlén (Kulturella Perspektiv)
This article is an empirical study of a segregated area in the town of Uppsala, and of the building intentions that failed. The planners focused on building different kinds of housing, not realizing that it would make a distinction between immigrants and Swedes. We argue that agents are needed on more than one level to form an integrated society and that the individual standpoint is the key. We focus on two examples of integration agents, the church and the school. Even though the Swedes in the area talked about the benefits of a multicultural society, they did not reach out to their immigrant neighbours because they did not see them as neighbours.